APONTAMENTOS INICIAIS- YARA GUASQUE: Do Pictórico Ao Digital (Palíndromo, 2013)
This article aims to analyze and record the transition from pictorial to digital in thought and production of the artist Yara Guasque, Professor of Visual Arts at the University of the State of Santa Catarina and researcher in art and technology. Her artistic career and intellectual moves from a pictorial production in the 80s and 90s, focused on large monochrome paintings by applying tempera on canvas, in which we find formal questions such as color and size, that approach her work of abstract expressionist artists of the decade 50, especially Mark Rothko, artist closer. Then she moved to the field of digital arts from the 2000s, whose works become even more experimental and collaborative. Her way is symptomatic of the current paradigm shift analog /digital, the article seeks to analyze the crossings of the concept of immersion in both pictorial and digital production performed by the artist. Starting from the immersive possibilities of pictorial field comes to the study of immersion in telepresence through experimental work carried out by groups Perforum Desterro and Perforum São Paulo, coordinated respectively by Yara Guasque and ArturMatuck.
Keywords: immersion; pictorial; abstract expressionism; art visual; telepresence